2006
DOI: 10.4049/jimmunol.177.7.4584
|View full text |Cite
|
Sign up to set email alerts
|

Repression of IFN-γ Induction of Class II Transactivator: A Role for PRDM1/Blimp-1 in Regulation of Cytokine Signaling

Abstract: MHC class II is expressed in restricted lineages and is modulated in response to pathogens and inflammatory stimuli. This expression is controlled by MHC CIITA, which is transcribed from multiple promoters. Although factors required for induction of CIITA are well characterized, less is known about the mechanisms leading to repression of this gene. During plasma cell differentiation, B lymphocyte-induced maturation protein-1 (PRDM1/Blimp-1) represses promoter (p)III of CIITA, responsible for constitutive expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 46 publications
3
60
0
Order By: Relevance
“…This footprinting assay also detected protein-DNA interactions in myeloma cells at the CIITA pIV IRF-E site that are similar before and after treatment with IFN-γ. We and others have recently demonstrated that the CIITA pIV IRF-E site is a binding site for the PRD-IBF1/Blimp-1 repressor (Tooze et al, 2006;Chen et al, 2007). It is possible that PRD-IBF1/Blimp-1 binds the IRF-E site in untreated myeloma cells and that this binding is replaced after treatment with IFN-γ by IRF-1 and IRF-2, which make similar contacts at this site and activate CIITA pIV expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This footprinting assay also detected protein-DNA interactions in myeloma cells at the CIITA pIV IRF-E site that are similar before and after treatment with IFN-γ. We and others have recently demonstrated that the CIITA pIV IRF-E site is a binding site for the PRD-IBF1/Blimp-1 repressor (Tooze et al, 2006;Chen et al, 2007). It is possible that PRD-IBF1/Blimp-1 binds the IRF-E site in untreated myeloma cells and that this binding is replaced after treatment with IFN-γ by IRF-1 and IRF-2, which make similar contacts at this site and activate CIITA pIV expression.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated CIITA type IV promoter activity that is up regulated by IFN-γ in B lymphocytes (Piskurich et al, 2006). We and others have also recently shown that this promoter, like pIII, is a candidate for repression by PRDI-BF1/Blimp-1 (Tooze et al, 2006;Chen et al, 2007). Since CIITA regulation is complex and cell-type specific, understanding its regulation in multiple myeloma requires the study of mechanisms of CIITA transcription as they relate specifically to these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression vectors encoding full-length (FL) BLIMP-1, IRF-1, and IRF-2 have been described previously (30). An expression vector encoding IDO1 was generated by amplifying cDNA using primers (5Ј-ATAGAATTCG CCACCATGGCACACGCTATGGA-3Ј and 5Ј-ATATGTCGACTTAACC TTCCTTCAAAA-3Ј) and cloned into the modified pIRES2-EGFP vector incorporating an N-terminal Myc epitope tag as previously described (30).…”
Section: Expression Vectors and Transfectionsmentioning
confidence: 99%
“…Work from our laboratory has shown that BLIMP-1 is indeed capable of repressing genes regulated by IFN-␥ (30,31). In these examples, BLIMP-1 mediates repression through direct competition with IFN regulatory factors (IRFs) at the IRF-E sites contained within their promoters.…”
mentioning
confidence: 99%